2012
DOI: 10.1002/elps.201100660
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of novel Alzheimer's disease proteomic cerebrospinal fluid biomarkers during intravenous immunoglobulin therapy

Abstract: Intravenous immunoglobulin (IVIg) therapy has shown promising results in treating Alzheimer's disease (AD). In this study, a Random Forest classification model was used to identify possible effects of IVIg on a group of eight subjects who underwent immunotherapy. Cerebrospinal fluid (CSF) samples from eight AD subjects who underwent IVIg therapy were collected before the therapy, after six months of therapy, and after a three-month drug washout period. Samples were analyzed using two-dimensional gel electropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A total of 23 AD biomarkers were studies in these patients by collecting CSF from spinal taps before initiation of therapy, 6 months afterward and after 3 month wash-out. Out of eight study subjects, significant improvement in biomarkers was seen in six subjects after six month therapy, which gradually returned to baseline levels after IVIg washout (Shayan et al, 2012). Nonetheless, in two recent trials, no significant slowing of AD progression could be documented (Dodel et al, 2013; Lemere, 2013).…”
Section: The Past Passive Immunization Experience For Admentioning
confidence: 99%
“…A total of 23 AD biomarkers were studies in these patients by collecting CSF from spinal taps before initiation of therapy, 6 months afterward and after 3 month wash-out. Out of eight study subjects, significant improvement in biomarkers was seen in six subjects after six month therapy, which gradually returned to baseline levels after IVIg washout (Shayan et al, 2012). Nonetheless, in two recent trials, no significant slowing of AD progression could be documented (Dodel et al, 2013; Lemere, 2013).…”
Section: The Past Passive Immunization Experience For Admentioning
confidence: 99%
“…A panel of 23 putative diagnostic CSF AD biomarkers was analyzed in these patients. Six of the 8 subjects showing improvements in these markers after 6 months of therapy, which reverted to baseline after IVIG wash-out [88]. However, in two more recent trials no significant slowing of AD progression was demonstrated [30,89].…”
Section: The Past Passive Immunization Experience For Admentioning
confidence: 99%
“…The level of anti-Aβ antibodies in the serum from AD patients increased in proportion to the IVIg dose administered, and CSF Aβ decreased significantly at 6 months of continued treatment, then returned to baseline when treatment was stopped, and decreased again with continuous IVIg treatment, indicating that the naturally occurring anti-Aβ antibodies mobilized Aβ from brain. Mini-mental state scores increased an average of 2.5 points with 6 months of treatment and remained stable with treatment was continued 5457. In a phase II dose-finding clinical study performed in the US and Germany in which AD patients also received IVIg injections (Octagam ® , Octapharma, Toronto, ON, Canada), the main focus was on the safety profile of this therapy 58.…”
Section: Clinical Human Studies: Anti-aβ Immunizationmentioning
confidence: 99%
“…Mini-mental state scores increased an average of 2.5 points with 6 months of treatment and remained stable with treatment was continued. 54 57 In a phase II dose-finding clinical study performed in the US and Germany in which AD patients also received IVIg injections (Octagam ® , Octapharma, Toronto, ON, Canada), the main focus was on the safety profile of this therapy. 58 In the 6-month treatment period, 14% of patients showed brain microbleeds and one patient had an ischemic stroke, both of which are known side effects of IVIg therapy.…”
Section: Clinical Human Studies: Anti-aβ Immunizationmentioning
confidence: 99%